2023
DOI: 10.1108/jsbed-06-2022-0269
|View full text |Cite
|
Sign up to set email alerts
|

Learning from entrepreneurial failure: examining attribution and contextual factors of small- and medium-sized enterprises in Indonesia

Abstract: PurposeThis study's main objective is to examine the effect of learning from entrepreneurial failure on performance, with a type of failure as a moderator variable. Interactions between internal and external causes of failure and learning from entrepreneurial failure are also investigated, as well as entrepreneurs' aspects (i.e. age, experience and education) and organisational contextual factors (i.e. size, sector and location).Design/methodology/approachThis study employed a hypothetico-deductive approach th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 71 publications
0
8
0
2
Order By: Relevance
“…There are many significant challenges that Indonesian MSMEs must overcome to adopt and operate an ERPbased information management system. One of the Nur Hasanah 1 , Dhanar lntan Surya Saputra [47], [48]. In addition, the need for more human resources trained in IT is also a challenge [49], [50].…”
Section: Barriers and Challenges In The Adoption And Implementation O...mentioning
confidence: 99%
“…There are many significant challenges that Indonesian MSMEs must overcome to adopt and operate an ERPbased information management system. One of the Nur Hasanah 1 , Dhanar lntan Surya Saputra [47], [48]. In addition, the need for more human resources trained in IT is also a challenge [49], [50].…”
Section: Barriers and Challenges In The Adoption And Implementation O...mentioning
confidence: 99%
“…Asimismo, Johnson et al (1997); y, Munawaroh et al (2023), plantean que no todos los individuos reaccionan de la misma manera ante el fracaso empresarial. Mientras que, en algunos, impulsa a la pérdida de la motivación y el abatimiento, en otros, estimula mayor dedicación en la búsqueda del éxito.…”
Section: El Fracaso Empresarialunclassified
“…En esta línea, se encuentran los enfoques: Organizacional, individuos, y recursos y capacidades. Por otra parte, los hallazgos evidencian que, existen estudios que utilizan el fracaso empresarial como una variable independiente, cuyas repercusiones pueden ser negativas (Mellahi y Wilkinson, 2004;Hazak y Mannasoo, 2007;García-Marí et al, 2016;Zizi et al, 2022;Lee, Wiklund et al, 2022); o positivas (Johnson et al,1997;Knott y Posen, 2005;McGrath, 2011;Lee, Simmons et al, 2022;Munawaroh et al, 2023).…”
Section: El Fracaso Empresarial Usado Como Variable Independienteunclassified
“…Discussions of causal mechanisms within the evolution of and complex interactions among entrepreneurial ecosystem elements have not received adequate attention until recently (Wurth et al, 2021;Audretsch et al, 2021;Stam & van de Ven, 2019;Stam & Spiegel, 2017;Alvedalen & Boschman, 2017). Cause-effect relationships among entrepreneurial ecosystem elements are especially important for efficient entrepreneurial decisions as well as entrepreneurial learning (Munawaroh et al, 2023), which has been identified as a key ingredient for entrepreneurial survival and success (Shen et al, 2021). However, even though the entrepreneurial ecosystem point of view is inherently time-dependent (Audretsch et al, 2021), the role of time in these multifaceted and dynamic relationships has not been explicitly considered.…”
Section: Introductionmentioning
confidence: 99%
“…The cost of wrong attribution of the sources of business challenges or failure on such a large scale can be significant in terms of the amounts of resources expended in fighting wrong causes. Moreover, such attribution error can hamper the efforts of stakeholders, especially entrepreneurs and entrepreneurship educators, towards improving entrepreneurial learning for better business outcomes (Munawaroh et al, 2023;Riar et al, 2021).…”
Section: Introductionmentioning
confidence: 99%